Sharing of Personal Sanitary Kits as One Risk Factor of Horizontal Transmission of Hepatitis B among Children Resident at Orphanage - Kambuno, Norma Tiku; Octrysdey, Karol; Nurdin, Kuntum Ekawati; Novicadlitha, Yoan; Barung, Elisabeth N.; Hafid, Fahmy (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Hepatitis B is a disease that infects the liver and is caused by the infection of a hepatitis B virus (HBV), and is becoming a global health issue, especially in developing countries including Indonesia. Hepatitis B can be transmitted through several ways such as infected bodily fluids. Indeed, children who live together in an orphanage are prone to having a high chance of transmitting Hepatitis B to each other. AIM: The purpose of this study was to analyze the factors associated with the prevalence of infected Hepatitis B. METHODS: This research used casecontrol study methodology by taking 15 positive case samples and 33 controlled uninfected patients and was conducted in six orphanages in Kupang Municipality in NTT between July 2019 and November 2019. There were 310 orphanage residents participating in this research. RESULTS: The research denotes that variables of using a shared toothbrush, nail clipper, and shaver show a significant connection with their Hepatitis B status (p < 0.05). A further analysis also indicates that using a shared shaver and toothbrush for 12.6 times has a high risk of being infected by Hepatitis B compared to those who do not share their personal items. CONCLUSION: Vaccinations and meeting the basic needs of every child in orphanages are essential in order to minimize the risk of Hepatitis B transmission.